2016
DOI: 10.1002/hed.24356
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and relevance of level I substation node counts in oropharyngeal carcinoma

Abstract: In oropharyngeal carcinoma, substation level I node quantification is feasible and relevant. This study shows a 5% risk to level I with metastasis in 3 different substations. © 2016 Wiley Periodicals, Inc. Head Neck 38:1194-1200, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Studies have shown an occult metastasis rate of up to 5%–8% in level 1 nodes in oropharyngeal carcinoma 13 . We acknowledge that intraoperative frozen specimen of level 1B may miss microscopic tumor due to limited sampling and some tissue loss, but final permanent specimens in all our patients did not show any signs of malignancy.…”
Section: Discussionmentioning
confidence: 53%
“…Studies have shown an occult metastasis rate of up to 5%–8% in level 1 nodes in oropharyngeal carcinoma 13 . We acknowledge that intraoperative frozen specimen of level 1B may miss microscopic tumor due to limited sampling and some tissue loss, but final permanent specimens in all our patients did not show any signs of malignancy.…”
Section: Discussionmentioning
confidence: 53%